2020
DOI: 10.1159/000507183
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Dickkopf-1 (DKK-1) Glycoprotein and Calcific Deposits on Cardiac Valves and Carotid Intimal-Medial Thickness in Hemodialysis Patients

Abstract: Background: Cardiac valve calcification (CVC) is common in hemodialysis (HD) patients, and associated with cardiovascular and all-cause mortality. Once believed to be a passive process, it is now understood that the Wnt signaling pathway has a major role. The aim of the current study was to assess the relationship between circulating DKK-1, a negative regulator of the Wnt signaling pathway, and CVC, as well as carotid intimal-medial thickness (CIMT) in HD patients. Methods: We enrolled 74 consecutive adults on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Consistent with previous studies [14, 15], the Kaplan-Meier test showed that patient survival was significantly lower in the CVC group than in the non-CVC group. The PSM method was applied to reduce potential confounding factors.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies [14, 15], the Kaplan-Meier test showed that patient survival was significantly lower in the CVC group than in the non-CVC group. The PSM method was applied to reduce potential confounding factors.…”
Section: Discussionsupporting
confidence: 90%
“…It is well known that Wnt- β -catenin signaling pathway inhibition by sclerostin and Dkk-1 protects against cardiac AV and MV calcifications and both have a significant negative correlation with both valves' calcification [ 41 , 42 ]. Our study revealed that AVC and MVC had a significant negative correlation with sclerostin but a nonsignificant negative correlation with Dkk-1 which coincides with Yang et al, 2015, who reported that circulating sclerostin but not Dkk-1 is inversely associated with aortic calcifications and future cardiovascular events [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, platelets release DKK-1 glycoprotein that acts as a potent antagonist to the Wnt-β-catenin signaling pathway. As a consequence, runt-related transcription factor 2 (Runx2), which is a canonical Wnt target and an osteogenic marker, gets activated ( 14 , 15 ). The upregulation of Runx2 by DKK-1 enhances the fibrotic mineralization of aortic endothelial cells under osteogenic conditions ( 13 ).…”
Section: Implications Of Platelets In Native Aortic Valve Stenosismentioning
confidence: 99%
“…Furthermore, the inhibition of DKK-1 with a neutralizing antibody, abolished interleukin (IL)-8 and MCP-1 in human umbilical vein endothelial cells that were activated by platelets ( 16 , 17 ). Moreover, a recent clinical showed that DKK1 was associated with calcific deposits on cardiac valves in hemodialysis patients ( 15 ). In addition to the role of platelets in the blood vascular network, they mediate the formation lymphatic vessels during embryonic development and prevent the mixing of blood to the lymphatic network ( 18 ).…”
Section: Implications Of Platelets In Native Aortic Valve Stenosismentioning
confidence: 99%